2023
DOI: 10.1021/acsnano.3c02915
|View full text |Cite
|
Sign up to set email alerts
|

Deformation Coupled Moiré Mapping of Superlubricity in Graphene

Abstract: The ultralow friction of two-dimensional (2D) materials, commonly referred to as superlubricity, has been associated with Moirésuperlattices (MSLs). While MSLs have been shown to play a crucial role in achieving superlubricity, the long-standing challenge of achieving superlubricity in engineering has been attributed to surface roughness, which tends to destroy MSLs. Here, we show via molecular dynamics simulations that MSLs alone are not capable of capturing the friction behavior of a multilayer-graphene-coa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…Nevertheless, the lower graphene is under higher strain than the top, and its lattice constant is somewhat different from the top under higher downward strain. The different levels of strain from top graphene to lower one induces a mismatch between their lattice constants, [ 30 , 46 , 58 ] which leads to an incommensurate state. Besides, analysis of the system energy supports the energetically favorable formation of GMS on a sphere, where the system energy decreases from −79 036 eV (at 0 ps) to −79 186 eV (at 75 ps) (Figure 5d ).…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, the lower graphene is under higher strain than the top, and its lattice constant is somewhat different from the top under higher downward strain. The different levels of strain from top graphene to lower one induces a mismatch between their lattice constants, [ 30 , 46 , 58 ] which leads to an incommensurate state. Besides, analysis of the system energy supports the energetically favorable formation of GMS on a sphere, where the system energy decreases from −79 036 eV (at 0 ps) to −79 186 eV (at 75 ps) (Figure 5d ).…”
Section: Resultsmentioning
confidence: 99%
“…Ruan et al [78] found that the ultralow friction and the reduction of the friction coefficient with the increase of the rotated graphdiyne bilayers moiré lattice size are closely related to the interfacial energetics and charge density as well as the atomic arrangement. Bai et al [79] used MD simulations to illustrate that only moiré superlattices cannot capture the friction behavior of a multilayer-graphene-coated substrate since the friction changes significantly as the graphene coating thickness increases. Their simulations showed that the interfacial contact distances and frictional behaviors are determined by a competition between interfacial moiré superlattice interactions and out-of-plane deformation of the surface as shown in figures 5(e)-(g).…”
Section: Moiré Supperlatticementioning
confidence: 99%
“…Based on this, how the persistence of moiré superlattice shape-induced superlubricity is affected by the twist angle and contact size was investigated, noteworthily, a critical twist angle of 1.5 • and a critical ratio of the contact size D to moiré period (the length of the strain soliton) [100]; L m , are required for robust superlubricity (Figure 7(a 1 ,a 2 )) [96]. The tribological behavior of a multilayer graphene moiré superlattice was further investigated by considering the effect of elastic deformation on the moiré superlattice shape-induced superlubricity [108]. Thicker 2D materials with smaller out-of-plane deformations and stronger interlaminar interactions reduce corresponding moiré superlattice periods, resulting in a lower friction and a higher sliding stability (Figure 7b).…”
Section: Moiré Superlatticementioning
confidence: 99%
“…Additionally, the α-P/β-P heterostructures always maintain the shape of linear stripes, as shown in Figure 7d. In addition, a load-independent, low-anisotropic, ultra-low friction structure was achieved by simulating the moiré superlattice Reprinted from [108], copyright (2023), with permission from American Chemical Society. (c) Frictional behavior of twisted bilayer graphdiyne by controlling the angle to change the size of moiré superlattice (MSL).…”
Section: Moiré Superlatticementioning
confidence: 99%